Menafsirkan Tanda-tanda Bedah Plastik: Analisis Semiotik - Ika Aliyatur; Shanty Duwila; Yulis Setyowati (EL2J (English Language and Literature Journal), 2023)
This study utilizes Charles Sanders Peirce's semiotic framework, concentrating on the interpretation of signifiers associated with plastic surgery. A particular emphasis is placed on the "Male Rhinoplasty" page as a case study, where icons, indexes, and symbols embedded in both images and texts are scrutinized across different sections of the website. Employing a qualitative approach, the study involves meticulous analysis of ten images extracted from the "Male Plastic Surgery" page. Among these, the study identifies 13 icons, 12 indexes, and 18 symbols, all of which serve as visual cues to not only enrich user experience but also evoke emotional responses that engage potential patients. The implications of these findings underscore the comprehensive communication strategy employed by ID Hospital's website. By adeptly incorporating Peirce's semiotic principles, the website constructs a multifaceted narrative concerning male rhinoplasty that is both visually captivating and emotionally resonant. This research not only sheds light on the semiotic complexities within the realm of plastic surgery communication but also provides insights into how websites can effectively employ visual and textual elements to convey intricate messages.